Influence of moral intensity, attitude and religiosity towards ethical awareness, judgement and intention among hotel managers in Malaysia - Chan, Ling Meng (2019)
Given the high rise of unethical conduct at workplace, there is a need to understand the nature of hotel first line managers’ ethical decision intention for both academics and organizational setting. In particular, researchers try to identify the factors that encourage / prohibit them to reason and behave ethically in order to derive a prescriptive guidance that can enhance the process, while practicing managers hope to develop policies and programs that strengthened employees’ ethical resolve on the job. Past studies mainly focused on the ethics behavioral theories by component/s, hence there is a need for researcher to identify how the ethical decisions making process is work with the influences of the selected variables. In this study, an integrated model developed from the theories of Positive Theory of Marketing Ethics, and Bratman’ Belief–Desire–Intention model to explain the research framework. Furthermore, based on this integrated model, the ethical decision intention component (ethical awareness, ethical judgment and ethical intention) are examined how their relationship towards each other, especially for ethical awareness. Researcher has employed survey based approach to meet the study’s objectives and self administrated questionnaires were used to gather data from 300 first line managers who work in 4 and 5-star hotels in Malaysia respectively. This survey consists of three different sections: 1) two fictitious ethical scenarios from Stevens (2001) to measure how respondents make their ethical decision intention with the influences of moral intensity; 2) instrumentation measurement for the variables of attitude and religious; and 3) demographic profile of respondents. The research hypothesis were examined through the use of quantitative statistical tests, which it employed SPSS version 25 and Smart-PLS version 3.0 software package to analyze the collected data. From the findings, moral intensity, attitude and religiosity explained nearly half of variance (46.80%) of ethical awareness, while moral intensity and ethical awareness explained majority of variance (65.70%) of ethical judgment. Besides that, ethical judgment explained 60.10% of ethical intention of managers when they engaging the decision making process. In addition, moral intensity is the strongest predictor in influencing managers’ decision making process when encounter ethical dilemma. This indicated that the importance of moral issues can encourage managers to have better sensitivity, higher evaluation and more ethical intention to act ethically right when encounter moral dilemma. Subsequently, if the moral issue is less importance, manager may perceive it and engage less ethically right when making decision. There is a relationship between the components of ethical decision making process, where ethical awareness and ethical judgment are playing the mediating role in enhancing individuals to make ethically right decision. This has not been done by the past studies, as most researchers only focused on assessing individual components with environmental factors. These significance findings make a unique contribution towards the development of moral theories, as researchers will not perceived them as individual but a comprehensive process to aware, evaluate and intend to act morally right. Through the findings of this study, it urges organizations to emphasize the importance of the ethical dilemma in their professional education at both the initial stage and through ongoing professional development. In the indicative content of the syllabi, there is only glancing recognition of ethics and professionalism, and occasionally reference to principles of equity, fairness, fundamental rights and obligations. As much as ethical discussion needs to be mainstreamed as a legitimate part of branch and national professional discourse, the foundation for this must be laid through the professional qualification scheme. As the conclusion of the research study, the findings suggested that the influences of attitude, religiosity and moral intensity are playing an important role in influencing how managers engage in their decision making process when encounter ethical dilemma.